PENERAPAN PEMBANGKIT TENAGA LISTRIK TENAGA BAYU SKALA KECIL SEBAGAI MEDIA PEMBELAJARAN DI SMK NEGERI 1 WONOSARI KABUPATEN MALANG - Awan Awan; Abraham Lomi; Abdul Hamid (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2021)
Sumberdem Village is located in Wonosari District, Malang Regency with an area of ​​426,310 Ha. The village was divided into four hamlets, namely Sumberingin, Rekesan, Duren Gede and Sumber Gelang hamlets. Located on the slopes of Mount Kawi, Sumberdem Village has a population of 4686 people consisting of 2328 men and 2358 women. These residents are members of 1296 families which are divided into five categories, namely Pre-prosperous 125 families, Prosperous I as many as 421 families, Prosperity II as many as 413 families, Prosperity III as many as 254 families, Prosperity III plus as many as 83 families. In terms of education level, the residents of Sumberdem Village have various levels of education. There were 145 illiterate people, 161 did not graduate from elementary school, 2912 people graduated from elementary school, 543 people graduated from junior high school, 381 people graduated from high school, 31 had bachelor's and master's degrees a1 person. SMKN 1 Wonosari where located in Sumberdem Village which has a major one of them is renewable energy. From this education sector, we can do service by providing grant assistance for small-scale wind power generation equipment as a learning medium for students of SMKN 1 Wonosari to provide knowledge and insight into wind power plant technology.